Tanda Dinamis Sedaap dan Dimensi Budaya Media Led dalam Respon Bersisi Dua Remaja - Harmayanthi, Vera Yulia (UI Scholars Hub, 2017)
The media today is characterized as scene and space evolution of advertising. LED Media (Light-Emitting Diode as advertising displays) is one of popular outdoor media spaces to advertise kinds of products’ scenes, such as drinks and foods. Cultural dimension of LED media is attractive, conventional media with advance technology and creative works. There are the creations of words which include visual pictures in moving appearance applied and appropriated into LED media landscape. It delivers the persuasive messages to individuals. Messages are pointed and adapted to individuals in age levels as the target. That is the most important to know their responses on those messages to be effectiveness. Perspective semiotics, Peirce theory, was used in this qualitative study as the way to know the level of individuals’ responses to products’ messages on LED media’s cultural dimension. The data were collected from teenagers who have experiences to the product. It is included external indicators like as age and sex in two-sided responses to some dynamical signs. They are both words and visual pictures offering a product messages Mie Sedaap on LED media, January 2017 in South Jakarta area. The results show, 1) dynamical signs of Sedaap in the relationship between representamen, object, and interpretant; 2) the relationship of dynamical signs Sedaap to cultural dimension on LED media; and 3) the levels of teenagers’ responses in two-sides like and dislike up to their decisions to buy products. All of them give values to show the effectiveness messages of cultural dimension on LED media, especially for teenagers.